(untitled) (Journal of Medical & Health Sciences Review, 2025)
An ovarian cyst is a pocket that grows in the ovary and is filled with fluid or semifluid solutions. Ovarian cysts are among the most frequent gynecological concerns affecting women of reproductive age, often linked with hormonal imbalances, lifestyle factors, and reproductive history. Despite their high prevalence, limited data is available in the local context to find the magnitude as well as associated factors. From May to August 2025, this cross-sectional study was carried out at Lady Reading Hospital’s Radiology Department in Peshawar. Finding out how common ovarian cysts occur in women of reproductive age and the danger factors that go along with them was the goal. Cochran’s formula was used to recruit 126 participants in total, with the following parameters set: 95% prevalence, 95% confidence interval along with 5% margin of error. Women between the ages of 15 and 60 who gave their informed consent were included; pregnant women, those with a history of ovarian cancer, oophorectomy, endocrine disorders, pelvic infections, incomplete records, or refusal to participate were excluded. Data were collected using a structured questionnaire divided into five sections: demographic profile, reproductive and menstrual history, medical and family history, lifestyle and risk factors, and clinical findings based on pelvic ultrasonography. Ethical clearance was obtained from the Institutional Review Board, and confidentiality was strictly maintained. Statistical analysis was carried out in SPSS version 27. Descriptive statistics (means, SD, frequencies, and percentages) shortened the data, while chi-square tests and cross tabulation determined associations and independent risk factors. A p-value <0.05 was considered statistically significant. The analysis revealed the 84.9% frequency of ovarian cysts in the study inhabitants and identified significant associations with demographic, reproductive, and lifestyle risk factors.